Influência da quantidade de prática no estudo de frequência de conhecimento de resultados na aprendizagem de habilidades motoras - Marluce Aparecida Fonseca (2013)
Frequency of knowledge of results (KR) is the amount of supplied KRs in a practice session, and it is classified in absolute (total of supplied KR) and relative frequency (proportion of KR in relation to number of practice trials). In studies of KR frequency, two possibilities are used to manipulate relative frequency: one, keeping absolute frequency and to vary amount of practice. Other, varying KR absolute frequency and to keep constant the number of practice trials. In comparing the results of KR frequency or keeping absolute frequency or keeping number of trials, it was observed the increase of amount of practice when absolute frequency is kept constant. The present research aimed to investigate the influence of amount of practice in the study of KR frequency in motor skills learning. Forty eight undergraduate students took part of the study. All of them were righted-hand and they had no previous experience in the task of salon-dart throwing to a target, with a posterior-anterior movement of dominant arm. Participants were set in four experimental groups (G100%, G33%a, G33%b e G11, 1%). In acquisition phase, groups G100% and G33%a performed 60 trials and received 60 and 20 KRs respectively. Groups G33%b and G11,1% performed 180 trials and received 60 and 20 KRs respectively. After acquisition phase, all groups performed ten trials with no KR in transfer test: immediate (TI), delayed (TA) and delayed (T3). Tests results showed that groups with reduced relative frequency presented less error and variability than high KR relative frequency group. Results in TA still showed that higher amount of practice was beneficial only to an optimal KR relative frequency. It was conclude that reduced relative frequency is more effective than high frequency (100%), and higher amount of practice contributes only to an optimal relative frequency.